Analisis Yuridis Terhadap Kedudukan Dan Fungsi Danantara Dalam Sistem Ketatanegaraan Indonesia - Tresno Utami, Wita; Juanda, Juanda (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to conduct a legal analysis of the position and function of Danantara (Daya Anagata Nusantara Investment Authority) as a sovereign wealth fund (SWF) institution within Indonesia's constitutional framework. Using a normative legal approach and literature review method, this research evaluates the legal foundation, institutional structure, accountability mechanisms, and international comparisons. The findings indicate that although Danantara has been established through Government Regulation No. 10 of 2025 and reinforced by Law No. 1 of 2025, its existence lacks adequate constitutional legitimacy. Danantara's role as a non-structural institution managing trillions in state assets requires a stronger legal basis and mandatory oversight mechanisms from the legislature and independent audit bodies. Furthermore, the insufficient implementation of the Santiago Principles such as transparent financial reporting, performance-based remuneration, and external audits leaves Danantara vulnerable to conflicts of interest and accountability risks. Compared to other SWFs like Temasek (Singapore), Khazanah Nasional (Malaysia), and China Investment Corporation (CIC), Danantara remains behind in governance practices and public engagement. This raises concerns about the long-term credibility of Danantara as a development instrument. Thus, a comprehensive structural and legal reform is urgently needed, including the enactment of a specific law and the establishment of a strong, independent oversight mechanism. Strengthening its legal status and governance system will ensure that Danantara not only contributes to economic growth but also upholds democratic accountability and constitutional order in Indonesia.